2011
DOI: 10.1111/j.1654-109x.2011.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration potential of the persistent soil seed bank in successional calcareous (alvar) grasslands in Estonia

Abstract: Questions: What is the overall restoration potential of the persistent soil seed bank of abandoned alvar grassland sites? To what degree does the share of characteristic alvar grassland species in the soil seed bank change during secondary succession from traditionally managed pasture towards stages overgrown by Corylus avellana and Juniperus communis?Location: Northern Estonia.Methods: The species composition of above-ground vegetation and the persistent soil seed bank were investigated in successional alvar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 57 publications
(67 reference statements)
0
52
2
2
Order By: Relevance
“…Propagule banks are considered crucial for re-establishment of pre-disturbance communities (Caners et al 2009;Kalamees et al 2012). Millennia-old peat layers exposed during peat extraction contain no viable propagules (Salonen 1994), and propagules arrived after peat extraction will be removed during stripping of the surface peat layer.…”
Section: Discussionmentioning
confidence: 99%
“…Propagule banks are considered crucial for re-establishment of pre-disturbance communities (Caners et al 2009;Kalamees et al 2012). Millennia-old peat layers exposed during peat extraction contain no viable propagules (Salonen 1994), and propagules arrived after peat extraction will be removed during stripping of the surface peat layer.…”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory evidence in the literature concerning the contribution of seed banks to the restoration of dry grasslands. Some authors argue that the soil seed bank can play an important role in the restoration of degraded sites, such as in Estonian calcareous grasslands (Kalamees et al ) or in Chinese sandy grasslands (Miao et al ). Our results showed that dry grassland specialist species already missing from the vegetation communities are no longer present in the soil seed bank.…”
Section: Discussionmentioning
confidence: 99%
“…Seed banks represent biodiversity reservoirs for grasslands and other ecosystems on a global scale, 31 playing an important role in the maintenance of genetic and species diversity, 32,33 and in the reestablishment of species lost from the above-ground vegetation. 34 Moreover, they reduce the risk of extinction as a consequence of a single environmental event such as drought or flooding. 35 Therefore, seed banks are often thought to buffer the responses of plant communities to climate variation, 36 providing potential resilience to disturbance or environmental shifts, 31 and to decrease extinction vulnerability under climate change.…”
Section: Introductionmentioning
confidence: 99%